Molecular mechanisms underlying gallic acid effects against cardiovascular diseases: An update review - Ghaidafeh Akbari (Mashhad University of Medical Sciences, 2019)
Objective: The prevalence of cardiovascular diseases (CVDs) is growing. CVDs are the major cause of mortality and have become one of the most important health challenges in developing countries. Gallic acid (GA) is a natural phytochemical which has been widely used against multiple conditions. The present review was designed to evaluate molecular mechanisms underlying the protective effects of this agent against CVDs. Material and Methods: Data discussed in this review were collected from the articles published in databases such as Science Direct, Scopus, PubMed, and Scientific Information Database between 1993 and 2018. Results: According to the experimental studies, GA has protective actions against CVDs through increasing antioxidant enzymes capacity, inhibition of lipid peroxidation and decreasing serum levels of cardiac marker enzymes, modulation of hemodynamic parameters, recovery of electrocardiogram aberrations, and preservation of histopathological changes. Conclusion: GA has potential cardioprotective action. Therefore, it has been suggested that this agent can be administered in underlying of CVDS.